The effect of supernatants of Lactobacillus casei against Porphyromonas gingivalis - Zainina, Iris Amelinda; Kusumawardani, Banun; Sari, Desi Sandra (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
Periodontitis is an inflammatory disease of the periodontal tissues primarily caused by Porphyromonas gingivalis (P. gingivalis). In recent years, probiotics have been proposed as a potential bacteriotherapeutic approach for periodontitis. Probiotic bacteria such as Lactobacillus casei (L. casei) are known to produce antibacterial compounds, which can be found in their culture supernatants. The ability of L. casei to grow and synthesize these substances depends on environmental factors, including pH. Based on preliminary findings, a pH of 6.5 was used in this study. This study aimed to evaluate the antibacterial activity of L. casei supernatant against P. gingivalis in vitro. The research employed an experimental post-test-only group design. Two control groups were included: a negative control (aquadest) and a positive control (0.2% chlorhexidine). The treatment groups received L. casei supernatant at volumes of 20 µl, 50 µl, and 80 µl, with incubation periods of 6, 12, and 24 hours. The results demonstrated that the L. casei supernatant exhibited the highest antibacterial activity against P. gingivalis at a volume of 80 µl after 12 hours of incubation. The Shapiro–Wilk test indicated that the data were normally distributed, while Levene’s test revealed a lack of homogeneity. Post hoc analysis showed significant differences among all treatment groups at the 12-hour incubation point. In conclusion, the supernatant of L. casei exhibits in vitro antibacterial activity against P. gingivalis.